Visionary Leadership for Techno-Pedagogical School Transformation: A Progressive Education Perspective - Triyana, Tinuk; Prayitno, Harun Joko; Sumardjoko, Bambang (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
This study aims to examine how visionary leadership contributes to techno-pedagogical transformation by integrating progressive educational values, technology-enhanced learning, and school improvement processes. Employing a conceptual research design, the study utilizes a critical literature review to synthesize theoretical and empirical scholarship on visionary leadership, progressive education, digital transformation, educational innovation, and professional learning. The analysis reveals that visionary leadership functions as a strategic, pedagogical, and ethical force that enables schools to align technological innovation with meaningful educational purposes. The findings indicate that techno-pedagogical transformation is facilitated through several interconnected mechanisms, including shared vision development, teacher empowerment, professional learning communities, collaborative learning cultures, and reflective technology integration. Building on these findings, the study proposes the Progressive Visionary Leadership Framework for Techno-Pedagogical School Transformation, which positions visionary leadership as a mediator between progressive educational principles and technology-enhanced learning practices. The framework highlights how democratic participation, experiential learning, collaboration, and learner agency can guide sustainable digital transformation in schools. This study contributes to the educational leadership literature by offering an integrative conceptual perspective that bridges leadership theory, progressive pedagogy, and digital innovation. The proposed framework provides a foundation for future empirical research and practical leadership initiatives aimed at fostering adaptive, inclusive, and sustainable learning schools in the digital era.